Transforming composite design by use of structural health monitoring - Liddel, Paul Daniel (Cranfield University, 2016)
Commercial composite aerospace structure is required to be designed and managed under the damage tolerant principle. Airworthiness is maintained through a process of regulated inspections and if required maintenance. Currently inspections use visual and assisted visual (non-destructive inspection - NDI) techniques. Damage tolerant operation is therefore reliant on inspectability. Unlike metal structure composite and adhesively bonded structure may show few if any recognisable indicators prior to rapid failure, either visually or using NDI. Although stringent manufacturing processes are demanded to best ensure components are fit for service strategies such as reducing stresses by oversizing components or in the case of bonded features additional mechanical fasteners may be included to allow operation with this potential structural uncertainty. Structural Heath Monitoring (SHM) uses data from in-situ sensors to assess the condition of the structure. If via SHM any uncertainty associated with difficult to inspect components could be eliminated less reliance would be required of additional structure or features allowing lighter and more efficient structure to be viable with no impact on current airworthiness demands. Despite much previous research no SHM system is in use with in-service composite or bonded aerospace components. When operating a structure under Damage-tolerance operational requirements damage must be positively identified to allow repairs to be made whist ensuring appropriate airworthiness demands are maintained. Such demands must also be met by structure inspected using SHM. Unlike previous studies this research combines the process of structural design and in-situ monitoring to address the issues identified. Termed SHM enabled design this approach allows the implementation of monitoring technology and the potential for benefits including the reduced reliance on inefficient additional structure to be viably included in actual structure ... [cont.].
Keywords: Bonded Joint; Damage tolerance; DIC; FEA; SHM enabled design; Strain